Incidence of amenorrhea and premature ovarian failure in women who underwent uterine fibroid embolization: single centre study - Al-Mailo, Tahany; Abdullah AlTakroni, Lulwa (International Journal of Scientific Research and Management (IJSRM), 2021)
Purpose: To retrospectively determine the incidence of amenorrhea and premature ovarian failure in women who underwent uterine fibroid embolization (UFE) in King Fahad Specialist Hospital in Dammam (KFSH-D).Patients and methods: All women who had undergone UFE in KFSH-D from August 2007 to October 2015 were included for a total of 82 patients. Follow up consisted of a questionnaire inquiring about symptoms, improvement after the procedure and whether menstruation resumed or not. The pre-procedure and post-procedure pelvis MRI as well as UFE images and reports were reviewed for all patients.  Results: One patient (1.5 %) was found to have amenorrhea out of the 67 patients we were able to contact. She was 52 years old at the time of UFE and had irregular period. Menstruation did not resume following UFE along with menopausal symptoms including night sweats, mood swings and irritability, likely due to premature ovarian failure (POF). The rest of patients had normal resumption of menses. Conclusion: The incidence of amenorrhea is less than what’s reported in the literature could be due to advances in UFE since its introduction as a treatment for uterine fibroids, likely due to advances in image quality, tans-catheter embolization equipments/techniques and embolic material used in UFE.